Traffic situation in Yerevan and ways to modernize with the help of current problem of traffic congestion - A. T. Sargsyan (Вестник СибАДИ, 2024)
Introduction. This article addresses the pressing issue of road traffic congestion in the capital of Armenia, Yerevan, and proposes a solution using the Automated Traffic Management System (ATMS). The introduction underscores the significance of effective traffic management in ensuring the safety and comfort of urban residents.Materials and methods. The analysis of the current situation raises concerns about traffic density, congestion, inefficient use of road resources, and their impact on the environment and citizens’ quality of life. In turn, the exploration of ATMS as a solution includes an explanation of the system’s concept, its benefits, and successful global implementation examples. The implementation plan for ATMS encompasses stages from data collection to traffic management, along with necessary technical and infrastructural changes. The assessment of costs and benefits underscores the economic and social components of anticipated outcomes.Conclusions. The introduction of automated traffic management systems (ATMS) leads to a significant reduction in transport delays at intersections by 10–20%, which reduces gasoline consumption for movement by 30%. The number of traffic accidents at intersections is reduced by 10–15%. This leads to economic benefits, improved road safety and improved environmental conditions in cities.